2019
DOI: 10.18805/ijare.a-5228
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Prescriptions under STCR-IPNS for Rice-Rice Cropping Sequence on An Inceptisol (Typic Ustropept)

Abstract: To develop fertilizer prescription equations based on soil test crop response (STCR) approach for rice-rice cropping sequence, trials were conducted at farmer’s field in Karikalampakkam village, U.T. of Puducherry, during 2015-16. Soil test data, yield and nutrient uptake by successive crops were recorded to calculate four basic parameters viz. nutrient required to produce one quintal of rice, contribution of nutrients from fertilizers, contribution of nutrients from soil and contribution of nutrients from FYM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The results also showed that uptake of nutrients were correlated positively with fruit yield and biomass yield of cucumber. Similar finding was also reported by Bagavathi et al (2019) and Luthra et al (2022). The nutrient requirement (NR) for producing one quintal of cucumber was 0.44kg N, 0.15 kg P 2 O 5 and 0.13kg K 2 O.…”
Section: Resultssupporting
confidence: 89%
“…The results also showed that uptake of nutrients were correlated positively with fruit yield and biomass yield of cucumber. Similar finding was also reported by Bagavathi et al (2019) and Luthra et al (2022). The nutrient requirement (NR) for producing one quintal of cucumber was 0.44kg N, 0.15 kg P 2 O 5 and 0.13kg K 2 O.…”
Section: Resultssupporting
confidence: 89%
“…The higher value of CF and CF* for potassium for the uptake in native soil source might be due to the interaction effects of the optimum supply of N and P, combined with the priming effects of potassium; this may increase the release of soil exchangeable and non-exchangeable potassium [50]. Similar findings were also reported by [27,51].…”
Section: Evolution Of Basic Parametersmentioning
confidence: 52%
“…The STVs for N, P, and K increased with increasing fertility levels, from strip I to strip III. Ammal et al [27] also reported that the average level of N, P, and K STVs increased with increasing fertility level, and the highest STVs were reported in strip III. The highest level STVs of N in strip III might be due to the addition of two folds more NPK fertilizers than the onefold and control [27].…”
Section: Fg Establishment Experimentsmentioning
confidence: 88%
See 2 more Smart Citations